A VENGEFUL EDUCATION? URBAN REVANCHISM, SEX WORK AND THE PENAL POLITICS OF JOHN SCHOOLS. Issue 1 (March 2015) - Cook, Ian R.
ABSTRACT This article considers how useful the urban revanchism thesis is in helping us understand the John School, a "mobile" educational programme that has been rolled out in the United States, Canada, the UK and South Korea which teaches those arrested for soliciting for the purposes of buying sex the negative consequences of their actions. The article begins by unpacking the urban revanchism thesis and bringing it into dialogue with ideas on punishment. It then draws on a case study of one English John School in the anonymized town of Redtown. It demonstrates that the operations and rationales of the Redtown John School have traces of revanchism and that they are also infused by ideas and practices of care. As a result it argues that the urban revanchism thesis illuminates some important aspects of the Redtown John School while silencing or misreading others. The article concludes therefore by calling for future research to think more broadly about punishment (rather than revanchism) in the city and its entanglements with care.